Tren onsumsi kopi robusta pada tingkat usia di OKU Selatan - Sebagustionnes, Angga; Oktarina, Yetty; Permatasari, Fifian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Coffee consumption in Indonesia is ranked number 1 in Southeast Asia, reaching 294,000 tons in 2019, increaase 13.9% compared to the previous year. This increase in consumption is in line to the increase in Indonesian coffee production at the end of 2019. The increase in consumption is supported by the development of new coffee shops that have opened hundreds of branches expansively with the concept of coffee to go- shop at affordable prices, thus creating a new trend among young people. The rapid growth of coffee shops in big cities, makes coffee is widely known to almost everyone regardless of age (Prakosa 2019). In South Ogan Komering Ulu (OKU) Regency, the tradition of drinking coffee has also become a hereditary culture. The geographical location of Ogan Komering Ulu Regency, which is one of the coffee-producing areas in South Sumatra, is also a driving force for people in this area to consume coffee. This study aims to review the productivity of Robusta coffee in South OKU and the level of household consumption of Robusta coffee in South OKU. This research was using time series data and analyzed using Ordinary Least Square (OLS). Based on the research conducted, it was found that the productivity level of Robusta Coffee South OKU Regency tends to decrease from year to year which is influenced by several natural factors, cultivation patterns and the availability of supporting facilities at the farmer level. However, coffee production has increased in line with the high level of consumption as well as trends and innovations in coffee offerings. Consumption and sales of coffee are highest among consumers who are in the age range of 15-19 years and the consumption tend to decline in the older age range.